THE POTENTIAL HEURISTIC OF THEORY OF CIVILIZATION BY NORBERT ELIAS TO STUDYING YOUTH VIOLENCE - di Napoli, Pablo Nahuel (Centro de Investigaciones y Estudios sobre Cultura y Sociedad, 2017)
This article aims to analyze the heuristic potential of the theory of civilizing processes proposed by Elias, to study the phenomenon of youth violence from a relational and process perspective. After specificating certain terms on which the criticisms are based on, we will present three reading keys. The first is framed in the sociogenetic and psychogenetic processes that, over time, impel the impairment of the use of physical force in the everyday relationship between individuals. The second key emphasizes generational conflict based on changes in the balance of power between the younger and older generations. Finally, we will analyze the possibility of decivilizing processes from cracking networks interdependence and return of external coercions. We will focus on two of the nodal works of the german sociologist to understand his theory of civilizing processes (and decivilizing). Those are Über den Prozess der Zivilisation (1939) and Studien über die Deutschen (1989). We believe that those works express the evolution of the procesual thought of the author.